Linguistic Diasporas, Narrative and Performance : The Irish in Argentina - O'Brien, Sarah (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores the present-day Irish Diaspora in Argentina, using oral narrative and a sociolinguistic theoretical framework to draw out the features that define contemporary Hiberno-Argentine identity. The author analyzes the spoken memories and discourses of Irish-Argentine descendants to trace the socio-political evolution of a bilingual, bicultural community from World War II to the present day. In so doing, O'Brien reveals a legacy of emigration that is without precedent in the global Irish Diaspora, and which is deeply relevant to today's global Irish citizenry in its challenging of preconceived notions of what it is to be Irish in the New World. As well as contributing to understandings of an immigrant linguistic journey over three generations, the book also provides a vital ethnographic portrait of an Irish descendant community that is acutely aware of its vulnerability and invisibility in an increasingly pluralistic South American society. This book will appeal to an interdisciplinary audience including scholars of migration, oral history, folklore, bilingualism, memory, sociolinguistics, narrative performance and Irish Diaspora studies. Sarah O'Brien is Assistant Professor of Applied Linguistics at Trinity College, Dublin, Ireland, and Director of the Centre for English Language Learning and Teaching there. She was formerly Director of Bilingual Education at Northern New Mexico College, USA, and a recipient of the IRCHSS doctoral award for her research on the Irish in Post-World War II Britain. Her publications explore linguistic and cultural acquisition in contemporary migrant communities with a particular focus on Latin America and Ireland.